Manufacturing of micro-textures on metals by nanosecond laser micromachining. Issue 1 (2nd January 2018) - Puoza, Julius Caesar; Hua, Xijun; Liu, Qiangxian; Kang, Zhengyang; Zhang, Peiyun
Abstract: The advantages and disadvantages between 'single pulse one time repeating at intervals' (SPI) and 'single pulse multiple times continuous' laser micromachining technology on surface textures were experimentally investigated. The micromachining of 45 steel, GCr15 steel and grey cast iron materials were also studied using the interval manufacturing technology. The efficiency of the laser processing technologies and quality of the ablated micro-dimples such as the diameter and depth were systematically analysed. The experimental results showed that, the 'single pulse one time repeating at intervals' (SPI) micromachining technology produced high quality dimples with less heat affected zone, smooth dimples with little slags due to its ability to effectively alleviate the negative heat accumulation effect to produce quality dimples as compared to the 'single pulse multiple times continuous' micromachining technology process. The diameter and depth of the micro-dimples increased generally with an increase in the laser fluence for all materials. The grey cast iron has the smaller ablation threshold with the largest dimple geometry due to its high laser absorption rate and the presence of more sulfur (S) and phosphorus (P) in the chemical composition, while GCr15 steel exhibited the smaller geometry due to its hardness.